Bura ura, kendu waiyo (rain falls, water rises): the tyranny of water insecurity and an agenda for abolition in Kodi (Sumba Island, Indonesia) - Fowler, Cynthia T. (Frontiers in Human Dynamics, 2023)
This article explores the dynamic links between transformations in freshwater ecosystems and social changes in the Kodi region of Sumba (Indonesia). Insights into the politics surrounding changing hydrosocial systems are generated by using a feminist anthropology approach together with critical development studies and intersectionality theory. In aligning with fellow feminists whose advocacy sometimes takes the form of scholarship, I lay out a five-prong strategy for collecting empirical evidence from persons who are vulnerable when hydrological systems change and offer eight principles for future development interventions. The argument related to the five-prong toolkit is that by conducting intensive, extensive, opportunistic, and longitudinal research and by allying with grassroots interlocutors, interventions into water systems can be based on better evidence and can be socially just. Three stories about Kodinese interactions with water and experiences with change are at the heart of this article and lead to the formulation of consequential conclusions. In the first story, birth, death, and relocation intersect with changes in the type of reservoir and the tools and vehicles used to manage water. In the second story—the origin for “tyranny” in the subtitle—vulnerability to food and water scarcity emerges and is politicized when a river's flow is altered. In the third story—the basis for “abolition” in the subtitle—hydrological interventions perpetrated by extrinsic governments correlate to surveillance and incarceration by the military and paramilitary. One research finding is that interventions by extrinsic agencies into the hydrology of four connected watersheds have altered hydrosocial relationships. Another finding is that as water's routes shift, people adjust to new conditions with mixed outcomes. A third conclusion is water utilities have differential benefits within the Kodi community. Fourth, benefits from water development have dispersed along already existing lines within the social structure. Finally, intracultural differences related to intersectional identities coincide with variations in access to natural and developed sources of water.